Composition and structure of helminth communities in eels Anguilla anguilla from Italian coastal lagoons - Kennedy, C; DI CAVE, DAVID; BERRILLI, FEDERICA; ORECCHIA, PAOLA (Cambridge University Press, 1997)
The composition and diversity of total and intestinal helminth component and infracommunities were determined in eels Anguilla anguilla from four shallow coastal lagoons near Rome. The lagoons differed principally in respect of their salinity. Only Lake Burano still received an input of freshwater, and both freshwater and marine helminth species were found in eels. In the other three lagoons all helminth species were marine or euryhaline and communities were dominated by digeneans. At component community level these three lagoons were far more similar to each other than to Lake Burano, but this distinction almost disappeared at infracommunity level. Species richness and diversity declined with increasing salinity at component community level but not at infracommunity level. Despite the changes and differences in helminth community composition, intestinal helminth infracommunity structure was very similar in all four lagoons and to that in eels from freshwater localities in Britain. The findings thus provide further and unexpected support for the view that some factor(s) other than supply side ones must be operating to produce the fundamental structural similarity in helminth communities in eels.